The Effects of Social Network on Fertility: The Case of Large Families in Russia - Goleva, Mariia (Journal of Economic Sociology, 2019)
The article attempts to answer the question: “How do large families appear in the contemporary world despite economic, social, and institutional constraints?” The study’s thesis focuses on the meso-level (social ties) in the research of processes of fertility. Results show that the typology of mechanisms affecting fertility behavior is based on the tradition of family research in the logic of social network analysis; this is relevant and productive for family studies. The analysis of 25 in-depth interviews with parents from large families reveals several conclusions about the functioning of the mechanisms affecting fertility behavior in the context of modern Russia. The interviews were conducted in Arkhangelsk, Moscow, Moscow region, and Vladimir region and were analyzed according to the Grounded Theory methodology. Data analysis showed that such processes as social contagion, social pressure, social learning, and social support expand the possibilities for a transition to a family with many children. Large families exist in a specific context, formed by the intersection of social ties, which include both existing contacts (kinship, friendship, parish) and emerging contacts on the basis of public organizations (e.g., centers of children’s creativity or family associations). In addition, a large family may become a generator of social capital, reciprocity, and trust in society. The data present fertility as a process embedded in social networks, offer a number of answers to the question “How do social networks influence fertility in large families?”, as well as identify perspectives for further research.